Use of essential oils for Nile tipalia breeders during breeding season - Freccia, André; Meurer, Fábio; Bittencourt Guimarães, Ana Tereza; Dena dos Santos, Lilian; Rosa da Silva, Lilian Carolina; Amancio, Tatiane; Bombardelli, Robie Allan (Revista Acadêmica Ciência Animal, 2020)
The present study aimed to evaluate the dietary supplementation of a commercial Saluto® compound containing essential oils extract of cinnamon (Cinnamomum zeylanicum), oregano (Origanum vulgare), rosemary (Rosmarinus officinalis) and pepper (Capsicum sp.) on breeding performance of female and male Nile tilapia (Oreochromis niloticus). The experiment had a completely randomized design with five treatments (0, 50, 100, 150, and 200 ppm of essential oil supplementation) and four repetitions during the breeding season of Nile tilapia. The apparent feed conversion, daily weight gain, condition factor, hepatosomatic index, gonadosomatic index, egg diameter, relative fecundity, egg weight, larvae yield, hatching rate, blood calcium and blood glucose levels were analyzed. In the correlations of variables at the female reproductive peak no statistical differences were found for the reproductive parameters and quality of the larvae. The nutritional additive inclusion did not impair reproductive parameters during the 120 days of evaluation, and inclusions above 50 ppm promoted an increase in the hepatosomatic index of Nile tilapia females during the reproductive season.